2018
DOI: 10.1002/ece3.4471
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic resource utilization and migration reconstruction with δ13C values of essential amino acids in the Cynoscion acoupa otolith

Abstract: With the increasing anthropogenic impacts on fish habitats, it has become more important to understand which primary resources sustain fish populations. This resource utilization can differ between fish life stages, and individuals can migrate between habitats in search of resources. Such lifetime information is difficult to obtain due to the large spatial and temporal scales of fish behavior. The otolith organic matrix has the potential to indicate this resource utilization and migration with δ13C values of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…However, advances using a persulfate-denitrifier method, allow N isotope measurements from small, individual otoliths (Cheng et al 2018;Lueders-Dumont et al 2018, 2020. For δ 13 C measurements of organics, otoliths are demineralized prior to isotopic analysis, facilitating measurements of organic C without dilution from the inorganic carbonate C that comprises most of the otolith mass (Godiksen et al 2019;Grønkjaer et al 2013;McMahon et al 2011aMcMahon et al , 2011bSirot et al 2017;Vane et al 2018a). Otoliths must be demineralized as the mineral fraction is a tracer of other, non-diet related variables (see Ecophysiology section).…”
Section: Methodological Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, advances using a persulfate-denitrifier method, allow N isotope measurements from small, individual otoliths (Cheng et al 2018;Lueders-Dumont et al 2018, 2020. For δ 13 C measurements of organics, otoliths are demineralized prior to isotopic analysis, facilitating measurements of organic C without dilution from the inorganic carbonate C that comprises most of the otolith mass (Godiksen et al 2019;Grønkjaer et al 2013;McMahon et al 2011aMcMahon et al , 2011bSirot et al 2017;Vane et al 2018a). Otoliths must be demineralized as the mineral fraction is a tracer of other, non-diet related variables (see Ecophysiology section).…”
Section: Methodological Developmentsmentioning
confidence: 99%
“…While the advantage of the persulfate-denitrifier method is the lower mass requirements for N, one of the primary advantages of EA-IRMS methods is that both δ 15 N and δ 13 C can be measured from the same otoliths. Micromill sampling, allowing for discrete analyses from juvenile and adult life history, is emerging for δ 15 N (Lueders-Dumont et al 2022;Vane et al 2018b) and for δ 13 C (Vane et al 2018a) analyses of the organic matrix, with higher resolution sampling tied to continued improvements in instrument sensitivity. δ 34 S values in otoliths have also emerged as a useful marker in freshwater systems to identify individuals who spent their early lives feeding in different aquatic habitats such as floodplains, rivers, and/or aquaculture facilities (Bell-Tilcock et al 2021;Johnson et al 2012;Weber et al 2002).…”
Section: Methodological Developmentsmentioning
confidence: 99%
“…The connectivity between the estuary and marine coastal zone provides unique attributes of habitat and important features for this species, serving as a nursery and growth area (Barletta-Bergan et al 2002; Barletta and Saint-Paul 2010), explaining its most common occurrence in estuaries or coastal environments with strong river influences. Vane et al (2018) suggest, from otoliths isotopic analysis studies, the existence of ontogenetic migration between the estuary and the coastal environment besides changes in resource utilization for C. acoupa. Therefore, these authors observed that juveniles and adults gradually use distinct environments (juveniles use estuarine while adults uses the marine coast) and overlap in intermediate stages of life, which may indicate that there is a regular movement between estuarine and coastal environments by C. acoupa juveniles.…”
Section: Distribution and Habitat Usementioning
confidence: 91%
“…Further studies should seek to distinguish this from pelagic microalgae carbon sources, e.g. if AAESS 13 C values differ between benthic and pelagic microalgae (Vane et al 2018). Assessing additional isotopes, such as bulk 34 S may also help to detangle benthic and pelagic sources in future studies (Hobson 1999).…”
Section: Mediterranean Sunfish Bulk Tissue 13 C and 15 Nmentioning
confidence: 99%